Intestinal Anastomotic Healing: What do We Know About Processes Behind Anastomotic Complications - Rosendorf, J.; Klicova, M.; Herrmann, I.; Anthis, A.; Cervenkova, L.; Palek, R.; Treska, V.; Liska, V. (Frontiers in Surgery, 2022)
Colorectal surgery has developed rapidly in the recent decades. Nevertheless, colorectal anastomotic leakage continues to appear postoperatively in unpleasant rates and leads to life-threatening conditions. The development of valid complication-preventing methods is inefficient in many aspects as we are still lacking knowledge about the basics of the process of anastomotic wound healing in the gastrointestinal tract. Without the proper understanding of the crucial mechanisms, research for prevention of anastomotic leakage is predestined to be unsuccessful. This review article discusses known pathophysiological mechanisms together with the most lately found processes to be further studied. The aim of the article is to facilitate the orientation in the topic, support the better understanding of known mechanisms and suggest promising possibilities and directions for further research.